Mediações no Sistema de Bibliotecas da Universidade Federal do Ceará na perspectiva da educação inclusiva - Sousa, Clemilda dos Santos (2016)
The inclusion of people with disabilities in education, despite many advances and achievements in the national and international level, has still faced many obstacles. Higher education, in the uniqueness of training professionals to contribute to the growth of society, has had its own challenges in the process of inclusion of people with disabilities. The University Library can contribute to this process, mediating the access to information and academic knowledge through its products and services. The research has, as main objective, to identify challenges and opportunities, in the access to academic knowledge, for students with visual impairments and their professors, having the University Library as a mediator. The study is characterized as exploratory of qualitative approach, taking the interview as a tool for data collection. The locus of the research is the Federal University of Ceará and its students with visual impairment and / or those who have low vision, as well as their professors in the subjects they find major and minor difficulties in accessing academic knowledge. The research concludes that the possible mediation in the context of inclusive education in Library System deals with the aspects of: attitudinal accessibility, digital communication and architectural aspects. Nevertheless, in order that the desired measurement becomes effective it is necessary to internally develop at the UFC Library System some Accessibility Policy, establishing accessibility parameters for the activities which will guide the services and products of the library in order that it becomes a promoter of the inclusive education in the academic environment. The most reported need, both by students and professors, is for books. The main suggestion is for a repository with the works in digital format. As for the training of the professors they recognize that they require more knowledge and suggest courses, workshops and training. As regards the inclusion policy most of the professors have a superficial knowledge. The students in their speech present a more consistent knowledge. Both students and teachers believe in the importance of the inclusion policy and consider the University Library important in the inclusion process.